Biogeography : an ecological and evolutionary approach - Cox, C. Barry (Christopher Barry), 1931- (Blackwell, 2005)
The latest edition of this highly successful and popular textbook has been completely revised and updated to include the latest developments in biogeography. It offers excellent insight into the multi-disciplinary nature of biogeography, providing the student with a sound historical base, up-to-date factual content and a clear explanation of current controversies. Its accessible style and well-balanced coverage will strongly appeal to students, while the successful synthesis of the many fields involved and the new format will attract a broad range of teachers and lecturers in biology, geography and environmental science departments.